Nitrogen-doped hierarchical porous carbons derived from biomass for oxygen reduction reaction - Wang, Min; Chen, Yao; Zhao, Shunsheng; Zhao, Cenkai; Wang, Guanxiong; Wu, Mingbo (Frontiers in Chemistry, 2023)
Nowadays biomass has become important sources for the synthesis of different carbon nanomaterials due to their low cost, easy accessibility, large quantity, and rapid regeneration properties. Although researchers have made great effort to convert different biomass into carbons for oxygen reduction reaction (ORR), few of these materials demonstrated good electrocatalytical performance in acidic medium. In this work, fresh daikon was selected as the precursor to synthesize three dimensional (3D) nitrogen doped carbons with hierarchical porous architecture by simple annealing treatment and NH3 activation. The daikon-derived material Daikon-NH3-900 exhibits excellent electrocatalytical performance towards oxygen reduction reaction in both alkaline and acidic medium. Besides, it also shows good durability, CO and methanol tolerance in different electrolytes. Daikon-NH3-900 was further applied as the cathode catalyst for proton exchange membrane (PEM) fuel cell and shows promising performance with a peak power density up to 245 W/g.